Content validity of the electronic faces thermometer scale for pain in children: is a picture worth more than a thousand words? - Höök, Angelica; Castor, Charlotte; Björk, Maria; Forsgren, Emma; Muszta, Anders; Nilsson, Stefan (Frontiers in Pain Research, 2024)
Introduction Early recognition of pain in children is crucial, and their self-report is the primary source of information. However, communication about pain in healthcare settings can be challenging. For non-verbal communication regarding different symptoms, children prefer digital tools. The electronic Faces Thermometer Scale (eFTS) utilizes a universal design with colors, face emojis, and numbers on an 11-point scale (0–10) for pain assessment. The aim of this study was to establish content validity of the eFTS for pain assessments in children. Methods A mixed methods design was used. The study took place at a university hospital in eastern Sweden, involving 102 children aged 8–17 years who visited outpatient clinics. Participants were presented with 17 pictures representing varying pain levels and asked to assess hypothetical pain using the eFTS. A think-aloud approach was employed, prompting children to verbalize their thoughts about assessments and the eFTS. Quantitative data were analyzed using descriptive and comparative statistics, together with a qualitative approach for analysis of think-aloud conversations. Results A total of 1,734 assessments of hypothetical pain using the eFTS were conducted. The eFTS differentiated between no pain (level 0–1) and pain (level 2–10). However, no clear agreement was found in the differentiation between hypothetical pain intensity levels (level 2–10). The analysis revealed that children utilized the entire scale, ranging from no pain to high pain, incorporating numbers, colors, and face emojis in their assessments. Discussion The variability in assessments was influenced by prior experiences, which had an impact on the statistical outcome in our study. However, employing the think-aloud method enhances our understanding of how children utilize the scale and perceive its design, including the incorporation of emotion-laden anchors. Children express a preference for using the eFTS to assess their pain during hospital visits.